Polia (Polia) richardsoni - Varga, Zoltán; Ronkay, Gábor; Nagy, Jenő; Ronkay, László (Zenodo, 2020)
Polia (Polia) richardsoni (Curtis, 1835) Hadena richardsoni Curtis, 1835, Appendix to John Ross Narrative of a Second Voyage 1835 : 72, pl. A, fig. 11. Type-locality: [Canada] 15 miles from River Tatchick (Eskimo name), 200 miles S of Port Bowen, very near Comptroller’s Island. Types: in coll. USNMW. Taxonomic notes. This circumpolar Holarctic species shows intense subspeciation in both continents; the taxonomic status of the described taxa is to be clarified yet. Published as part of Varga, Zoltán, Ronkay, Gábor, Nagy, Jenő & Ronkay, László, 2020, Contribution To The Taxonomy And Phylogeny Of The Genus Polia Ochsenheimer, 1816 (Noctuidae, Noctuinae, Hadenini): Species Groups And Pairs In The Holarctic Subgenus Polia S. Str., pp. 35-67 in Acta Zoologica Academiae Scientiarum Hungaricae 66 (1) on pages 50-51, DOI:10.17109/AZH.66.1.35.2020, http://zenodo.org/record/5734753